A Comprehensive Analysis of the Ukraine -Russia Battle Food Grain Lacks and Economic Impacts - Muhammad Ali; Abdoulrahman Aljounaidi; Fariba Azizzadeh; Al Harath Atiek; Sebastian Zupok; Mohammad Shahidul Islam (MultiTech Publisher, 2022)
Background- Ukraine and Russia both two-sided cover almost 24% of wheat to the world especially developing countries that depend on wheat apart from this they also import some other edible items. Aim- Thus the goal of the study is to analyze the damages of the Ukraine-Russia conflict on food grain shortage and other sectors' impacts. Methods- We used 2 country analyses Pakistan and Ethiopia to analyze the condition between the two continents Asia and Africa analysis included, GDP fallout, increasing unemployment rate, with the association of people suffering in urban and rural areas of both countries. Results- From the results, it is clearly indicated that due to the Russia-Ukraine conflict developing countries suffer economically, in the agriculture sector, and service and industry sectors. Conclusion- Concluding the remarks about the conflict is that developing countries are suffering from lack of wheat shortages, high commodity prices, market volatility, high inflation rate, disruption of supply-demand, and many other consequences. While policy implication the world's big countries must take initiative to preclude the Russia-Ukraine conflict to avoid further big losses and environmental damage as well